Algorithmic management consequences for work organisation and working conditions - Alex J. Wood (European Commission, Joint Research Centre (JRC), 2021)
The use of software algorithms to automate organisational functions traditionally carried out by human managers has been termed "algorithmic management" and identified in both platform work and conventional employment settings. Algorithmic management has been researched in greatest detail in the settings of platform work and warehousing but also noted to a lesser extent in retail, manufacturing, marketing, consultancy, banking, hotels, call centres, and among journalists, lawyers and the police. This working paper reviews industry examples from the above sectors along with more detailed case studies of platform work. Doing so enables the outlining of the main ways in which algorithms are deployed to automate workforce direction, evaluation and discipline. A new framework is presented for differentiating algorithmic management from algorithmic assistance and whether it constitutes partial, conditional, high, or full automation. The working paper also high-lights some potential consequences of algorithmic management for work organisation and working conditions. In particular, the existing evidence suggests that algorithmic management may accelerate and expand precarious fissured employment relations (via outsourcing, franchising, temporary work agencies, labour brokers and digital labour platforms). It may also worsen working conditions by increasing standardisation and reducing opportunities for discretion and intrinsic skill use. Evidence from platform work and logistics highlights the danger of algorithmic management intensifying work effort, creating new sources of algorithmic insecurity and fuelling workplace resistance. Finally, the implications for policy are considered and remedies to the potential harms of algorithmic management considered.
Keywords: 330; algorithmic management; Work organisation; Working conditions; platform work